2019
DOI: 10.3892/etm.2019.7211
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of NET‑1 suppresses proliferation and promotes apoptosis of hepatocellular carcinoma cells by activating the PI3K/AKT signaling pathway

Abstract: The present study aimed to elucidate the underlying mechanism of neuroepithelial cell transforming 1 (NET-1), a member of the Ras homolog gene family, in hepatocellular carcinoma (HCC). To determine the association between the expression of NET-1 and the proliferation and migration of MHCC97-H cells, the cells were transfected with NET-1 small interfering (si)RNA and si negative control. Following transfection with NET-1 siRNA, the proliferation rate of MHCC97-H cells decreased significantly and the percentage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 56 publications
(57 reference statements)
0
10
0
Order By: Relevance
“…Accumulating evidence suggests that the phosphatidylinositol-3-kinase/protein kinase B (PI3K/Akt) signaling pathway is vital for the growth, metabolism, apoptosis, metastasis, chemotherapy resistance of cancer cells [6,7]. PI3Ks are heterodimers, composed of one p110 catalytic subunit encoded by PIK3CA (p110α), PIK3CB (p110β) or PIK3CD (p110δ) and one p85 regulatory subunit encoded by PIK3R1 (p85α), PIK3R2 (p85β) or PIK3R3 (p85γ) [8]. Akt, a serine-threonine kinase, is directly activated by PI3K to promote cancer cells growth, survival and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulating evidence suggests that the phosphatidylinositol-3-kinase/protein kinase B (PI3K/Akt) signaling pathway is vital for the growth, metabolism, apoptosis, metastasis, chemotherapy resistance of cancer cells [6,7]. PI3Ks are heterodimers, composed of one p110 catalytic subunit encoded by PIK3CA (p110α), PIK3CB (p110β) or PIK3CD (p110δ) and one p85 regulatory subunit encoded by PIK3R1 (p85α), PIK3R2 (p85β) or PIK3R3 (p85γ) [8]. Akt, a serine-threonine kinase, is directly activated by PI3K to promote cancer cells growth, survival and metabolism.…”
Section: Introductionmentioning
confidence: 99%
“…erefore, overexpression of NET1 was closely related to malignant cellular biological behaviors [29] and was also associated with a variety of human cancers, including acute lymphoblastic leukemia [14], breast cancer [30], hepatocellular carcinoma [10], and non-small-cell lung cancer [15]. Consistently, bioinformatics validation, luciferase reporter assay, and western blotting analysis demonstrated that NET1 was directly and negatively targeted by miR-22 in both A549 and H1299 human NSCLC cell lines.…”
Section: Discussionmentioning
confidence: 68%
“…NET1 enhances OAC cell proliferation and invasion, and it regulates LPA-induced OAC cell migration [8]. NET1 relates to proliferation, metastasis, and TMN stages of hepatocellular carcinoma (HCC) and can promote the progression of HCC by modulating the PI3K/AKT signaling [9,10]. Meanwhile, NET1 is also an indicator of poor prognosis in HCC and adenocarcinoma of the oesophagogastric junction [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the PI3K-Akt signaling pathway, numerous studies have also reported its crucial role in the process of HCC. The PI3K-Akt signaling pathway has been widely reported to act as a key factor related to cell proliferation, invasion, metastasis, and apoptosis as well as the cell cycle [52][53][54][55][56]. Given that, we speculated that the molecular mechanism of CELSR3 in promoting cell proliferation, invasion, and migration, as well as inhibiting apoptosis may be closely associated with the cell cycle, DNA replication, and the PI3K-Akt signaling pathway through interacting with its co-expressed genes.…”
Section: Discussionmentioning
confidence: 93%